Generality and Shifts in Leaf Trait Relationships Between Alpine Aquatic and Terrestrial Herbaceous Plants on the Tibetan Plateau - Yang, Lei; Zhao, Haocun; Zuo, Zhenjun; Li, Xiangyan; Yu, Dan; Wang, Zhong (Frontiers in Ecology and Evolution, 2021)
Plant traits mirror both evolutionary and environmental filtering process with universal trait-trait relationships across plant groups. However, plants also develop unique traits precisely to different habitats, inducing deviations of the trait coupling relations. In this study, we aimed to compare the differences in leaf traits and examine the generality and shifts of trait-trait relationships between alpine aquatic and terrestrial herbaceous plants on the Tibetan Plateau, to explore the precise adaptive strategies of aquatic and terrestrial plants for its habitats. We measured mass-based and area-based leaf N and P concentrations, N:P ratios and specific leaf area (SLA) of aquatic and terrestrial herbaceous plants. Standardized major axis analysis were applied to build the correlations for every trait pairs of each plant group, and then to compare the differences in the trait-trait correlations among different plant groups. Leaf Nmass and Pmass of two groups of aquatic plants (emergent and submerged plants) were higher, but N:P ratios were lower than those of two groups of terrestrial plants (sedges and grasses). Submerged plants had extremely high SLA, while grasses had the lowest SLA. Nmass positively correlated with Pmass in three out of four plant groups. The two terrestrial plant groups had positive Nmass-SLA relationships but these two traits coupled weakly in aquatic plants. Pmass showed positive relationships to SLA in three out of four plant groups. Significant shifts of trait-trait relationships between aquatic and terrestrial plants were observed. In general, aquatic plants, especially submerged plants, are characterized by higher SLA, greater leaf nutrientmass than terrestrial plants, tend to pursue fast-return investment strategies, and represent the acquisitive end of leaf economics spectrum. The deviations of trait-trait relationships between different plant groups reveal the precise adaptions of submerged plants to the unique aquatic habitats.